2017
DOI: 10.3892/mmr.2017.7740
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dobesilate may alleviate diabetes-induced endothelial dysfunction and inflammation

Abstract: Diabetic kidney disease (DKD) is a leading cause of end-stage renal disease. However, the pathogenesis of DKD remains unclear, and no effective treatments for the disease are available. Thus, there is an urgent need to elucidate the pathogenic mechanisms of DKD and to develop more effective therapies for this disease. Human umbilical vein endothelial cells (HUVECs) were cultured using different D-glucose concentrations to determine the effect of high glucose (HG) on the cells. Alternatively, HUVECs were incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
(39 reference statements)
2
19
0
1
Order By: Relevance
“…Consistent with the anti-migratory function, CaD also abolished VEGF-induced polymerization of actin in lamellipodia-like structures. Zhou and colleagues have recently demonstrated an inhibition of endothelial cell proliferation and migration by CaD under hyperglycemic conditions [25], which they attributed to the corresponding changes in VEGF expression. Instead, and heparin (10 μg/ml) were pre-mixed and incubated at 37˚C for 60 min prior to HUVECs stimulation for 2 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the anti-migratory function, CaD also abolished VEGF-induced polymerization of actin in lamellipodia-like structures. Zhou and colleagues have recently demonstrated an inhibition of endothelial cell proliferation and migration by CaD under hyperglycemic conditions [25], which they attributed to the corresponding changes in VEGF expression. Instead, and heparin (10 μg/ml) were pre-mixed and incubated at 37˚C for 60 min prior to HUVECs stimulation for 2 min.…”
Section: Discussionmentioning
confidence: 99%
“…At present, CaD is approved in numerous countries for the treatment of diabetic retinopathy another important complication of diabetes mellitus and its efficacy has been analyzed in a recent meta-analysis [23,24]. Moreover, recent studies have demonstrated that CaD can be safely and effectively used to treat diabetic nephropathy in type 2 diabetic patients [25,26]. However, the pharmacology of CaD is poorly understood.…”
mentioning
confidence: 99%
“…In addition, our experiments show that CaD prevents the increase and upregulation/activation of several pro-inflammatory cytokines (IL-6, CXCL1, IL-1ß, TNF-α, and MCP-1) that play a significant role in renal-disease progression. Although the anti-inflammatory properties of CaD have been previously reported (42,46), to the best of our knowledge, our report is the first involving a diabetic-nephropathy animal model. These findings are therefore important due to the pivotal role of inflammation in the pathogenesis of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 77%
“…Consistent with the anti-migratory function, CaD also abolished VEGF-induced polymerization of actin in lamellipodia-like structures. Zhou and colleagues have recently demonstrated an inhibition of endothelial cell proliferation and migration by CaD under hyperglycemic conditions (42), which they attributed to the corresponding changes in VEGF expression. Instead, we demonstrate a direct effect of CaD on VEGF signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation